Strategi Konseling Kelompok Realitas untuk Mengembangkan Kemampuan Pengambilan Keputusan Karier Pada Siswa Kelas XI SMK Plus Pelita Nusantara - Butar-Butar, Dika Sonya; Nugroho, Andreas Rian; Gunawan, Ronny (Universitas Mathla'ul Anwar Banten, 2024)
This study aims to improve the career decision-making skills of students of SMK Plus Pelita Nusantara. The research method used is Quasi Experimental with the application of Nonequivalent Control Group Design which provides data collection before and after the implementation of group counseling. The population of this study were all grade XI students of SMK Plus Pelita Nusantara which amounted to 352 students. The sampling technique in this study used purposive sampling method. The number of samples in this study were 10 students who were selected based on the criteria determined by the researcher. The data that has been collected is analyzed using the t table test to test for significant differences between the pre-test and post-test scores with a significance value (2-tailed) p=0.000 which means the p value is smaller than 0.05 (<0.05). These results indicate that there is an increase in the average career decision making from the average experimental class pretest score of 69 and a posttest score of 77.4. The score in the control class with an average pretest score of 69.9 and a posttest score of 72.9. With these results, it can be concluded that reality group counseling is effective in developing students' career decision-making skills at SMK Plus Pelita Nusantara. KEYWORDS: Reality Group Counseling Strategies, Career Decision Making, Vocational School Students